Perencanaan Pajak dan Book Tax Differences terhadap Persistensi Laba dengan Variabel Moderating Kualitas Laba - Risti Dwi Lestari; Sistya Rachmawati (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
This study aims to analyze and find evidence of the effect of tax planning and book tax differences on earnings persistence with earnings quality as moderating variable. The data used is secondary data obtained from the financial statements of manufacturing companies listed on the Indonesian Stock Exchange for 4 years; namely 2014-2017 selected by purposive sampling method. This analytical method used to test the hypothesis in this study is multiple regression analysis.The results of this study indicate that the tax planning variable has a negative influence on earnings persistence. This is because tax planning is used to apply discretion policy of accounting in reducing company profit so it will reduce tax amount. Contra effect of tax planning causes low earnings persistence The company conducts tax planning to minimize the tax burden that is borne by companies that have a long-term focus so that profits can reflect future earnings (sustainable earnings). Whereas book tax differences do not have an influence on earnings persistence, this is possible because income and costs that are adjusted in fiscal reconciliation do not affect future earnings revisions. Lastly, earnings quality does not strengthen tax planning and book tax differences toward earnings persistence.